1991
DOI: 10.1149/1.2085411
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of  CO 2 at Intentionally Oxidized Copper Electrodes

Abstract: We observed CO2 reduction to CH3OH at various oxidized copper electrodes at 22~ The electrode types included anodized Cu foil, Cu foil thermally oxidized in air, and air-oxidized Cu electrodeposited on anodized or air-oxidized Ti foil. The highest rates to date, 1 • 10 4 mol cm -2 h -1 (geometrical area), were found using anodized Cu in 0.5M KHCO3, pH = 7.6, and -1.9 V (SCE). Faradaic yields for CH3OH depended on the current and reached about 240%. The onset potential for CH3OH formation was near -0.4 V (SCE).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
179
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(190 citation statements)
references
References 12 publications
7
179
3
1
Order By: Relevance
“…Interestingly, these values are remarkably higher than those obtained with the Cu plate, independently of the applied potential. This fact is in good agreement with previous findings where surfaces with copper oxides have shown higher activity for the reduction of protons than the Cu (0) sites for CO2 electroreduction to CH3OH, as demonstrated by Frese et al [15] where the electrochemical performance of Cu-based electrodes (i.e Cu foil, Cu foil thermally oxidized in air and air-oxidized Cu electrodeposited on anodized or airoxidized Ti foil) was compared, or as recently reported by Lan et al [23], where a larger amount of CH3OH was obtained for Cu(core)/CuO(shell) catalysts in 1 M KHCO3 at -1.72 V vs. Ag/AgCl than that amount obtained at a Cu foil.…”
Section:  Cyclic Voltammetric Characterizationsupporting
confidence: 94%
See 3 more Smart Citations
“…Interestingly, these values are remarkably higher than those obtained with the Cu plate, independently of the applied potential. This fact is in good agreement with previous findings where surfaces with copper oxides have shown higher activity for the reduction of protons than the Cu (0) sites for CO2 electroreduction to CH3OH, as demonstrated by Frese et al [15] where the electrochemical performance of Cu-based electrodes (i.e Cu foil, Cu foil thermally oxidized in air and air-oxidized Cu electrodeposited on anodized or airoxidized Ti foil) was compared, or as recently reported by Lan et al [23], where a larger amount of CH3OH was obtained for Cu(core)/CuO(shell) catalysts in 1 M KHCO3 at -1.72 V vs. Ag/AgCl than that amount obtained at a Cu foil.…”
Section:  Cyclic Voltammetric Characterizationsupporting
confidence: 94%
“…Finally, Table 4 compares the production of CH3OH, r, and efficiency, FE, at Cu2O (1) and Cu2O/ZnO (1:1)-based electrodes prepared in this study with previous results reported in literature for Cu-based surfaces, when different supporting electrolytes and cell configurations are applied [11,[15][16][17][18][19][20][21][22][23]. Further advances are still required in order to develop catalyst materials with optimal performance for practical applications.…”
Section:  Stability Of the Prepared Electrodesmentioning
confidence: 71%
See 2 more Smart Citations
“…[13] However,a major breakthrough was achieved by Frese in the 1990s, who reportedt he finding that Cu oxides can playamajor role in stabilizing the adsorbed CO to form adsorbed CHO that can be furtherr educed to form CH 3 OH. [167,185] Although the catalytic resultso btained by Frese were not feasible, (the faradaic efficiencies obtained for CH 3 OH formation were 240 %), the conclusion of the work paved the way for future research into CH 3 OH, as it is now understood that Cu + species play the major role in binding CHO species, whichdetermines the product selectivity for CH 3 OH. This knowledgew as invoked by Le et al who reported an electrodeposited Cu 2 Ot hin film that yielded aF E CH 3 OH value of 33 %a tÀ0.4 V. [168,186] This ascription was also supported by an oxide-derived Cu/C catalyst that demonstrated ah igh FE CH 3 OH of 40 %a ta na pplied potential of only À0.3 V ( Figure8).…”
Section: Cumentioning
confidence: 96%